Characterization of chromium species and distribution during Cr(VI) removal by biochar using confocal micro-X-ray fluorescence redox mapping and X-ray absorption spectroscopy. (January 2020) - Liu, Peng; Ptacek, Carol J.; Blowes, David W.; Finfrock, Y. Zou; Liu, YingYing
Graphical abstract: Highlights: Cr(VI) decreased from 50 to <0.02 mg/L by biochar at pH 2 with 8.8% in solution as Cr(III). Bulk XANES show only Cr(III) in solid phase, whereas micro-XANES show 0–36% Cr(VI). EXAFS indicate removed Cr in Cr(OH)3 form with same atomic structure of goethite. Confocal µ-XRF redox mapping show only Cr(III) in biochar at early reaction time. Reaction steps include electrostatic attraction, diffusion, reduction, ion exchange. Abstract: Biochar is an effective, environmentally sustainable material for removing Cr(VI) from water. Potential removal mechanisms include surface reactions or reactions within the biochar structure with direct bonding of Cr(VI) or reduction of Cr(VI) and bonding of the reduced Cr forms. Diffusion process and Cr(VI) and Cr(III) distributions in biochar particles have not been elucidated. Aqueous Cr(VI) removal experiments followed by solid-phase analyses were conducted to evaluate the effectiveness of raw and modified oak wood biochar for removing aqueous Cr(VI) and to further determine removal mechanisms. Results showed that concentrations of Cr(VI) decreased from 50 to <0.02 mg L −1 at initial pH 2 after 1 d using raw oak wood biochar, with 8.8% of the initial aqueous Cr reduced to Cr(III) in the solution. Similarly, effective removal of Cr(VI) was observed using polysulfide-modified biochar; whereas 54% of initial Cr(VI) was removed using HNO3 -treated biochar. Bulk X-ray absorption near-edge structure (XANES) analysis showed Cr is present as Cr(III) within the unmodified biochar, whereas confocal micro-XANES analysis showed the existence of Cr(VI) (0–36%) in selected spots and Cr(0) (43%) in one spot within a biochar sample collected after 30 min. Extended X-ray absorption fine structure (EXAFS) results showed the atomic structure of Cr within the unmodified biochar was similar to Cr(OH)3, with O and Cr in the first and second shells. Confocal micro-X-ray fluorescence imaging (CMXRFI) results indicated total Cr (tCr) was heterogeneously distributed in the imaged area with a higher intensity close to the particle surface. Redox mapping results indicated no Cr(VI) in the unmodified biochar collected at 30 min; Cr(III) was the primary form and also remained close to the surface at later time. The removal mechanisms likely involve electrostatic attraction and diffusion inside the particle, followed by reduction and ion exchange reactions.